2019
DOI: 10.1038/s41598-019-43639-z
|View full text |Cite
|
Sign up to set email alerts
|

Copper sulfide nanoparticles as high-performance cathode materials for Mg-ion batteries

Abstract: Rechargeable magnesium batteries are appealing as safe, low-cost systems with high-energy-density storage that employ predominantly dendrite-free magnesium metal as the anode. While significant progress has been achieved with magnesium electrolytes in recent years, the further development of Mg-ion batteries, however, is inherently limited by the lack of suitable cathode materials, mainly due to the slow diffusion of high-charge-density Mg-ions in the intercalation-type host structures and kinetic limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 54 publications
(40 reference statements)
0
55
0
Order By: Relevance
“…[ 57,58 ] These results agree with other reports of nano‐CuS prepared through a variety of methods: enhanced Mg 2+ diffusion kinetics leads to improved electrochemical performance which can be obtained by using nanoparticles to prepare Mg electrodes. [ 59,60 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 57,58 ] These results agree with other reports of nano‐CuS prepared through a variety of methods: enhanced Mg 2+ diffusion kinetics leads to improved electrochemical performance which can be obtained by using nanoparticles to prepare Mg electrodes. [ 59,60 ]…”
Section: Resultsmentioning
confidence: 99%
“…A reduction of molybdenum center (Mo 6+ +3e − →Mo 3+ ) or a combination of reduction of molybdenum center (Mo 6+ +2e − →Mo 4+ ) and copper center (Cu + +1e − →Cu 0 ) could be responsible for the electrochemical reaction with Mg 2+ ion. Indeed, the reduction of Cu + center causing the intercalation of Mg 2+ has been reported for the case of CuS cathode …”
Section: Figurementioning
confidence: 96%
“…In addition, localized surface plasmon resonance (LSPR) effects are exhibited in Cu 2-x S NP due to the high free carrier density, depending on stoichiometry and size [ 19 , 20 ]. Hence, Cu 2-x S NPs are suitable for nanostructured applications such as battery electrodes [ 21 ], photocatalysts [ 22 ], sensors [ 23 ], biomedical devices [ 24 ], and photovoltaic cells [ 25 ], as they provide unique properties that cannot be achieved using the traditional bulk materials. For example, Otelaja et al (2014) [ 26 ] demonstrated that the EPD films obtained from Cu 2-x S NPs dispersed in hexane exhibit a higher conductivity than those prepared by spin-casting.…”
Section: Introductionmentioning
confidence: 99%